Optimal Colorant Composition for Agateware Products at Lukita Ceramic Studio Yogyakarta (International Forum of Researchers and Lecturers, 2025)
This article explores the most effective dye composition for agateware ceramic products crafted at Lukita Ceramic Studio. Agateware is recognized for its distinctive marbled and layered color effects, achieved through the combination of different colored clays. To produce aesthetically pleasing and high-quality outcomes, the selection of appropriate colorants plays a crucial role. The primary aim of this study is to determine the ideal color combinations that enhance both the visual appeal and overall quality of agateware ceramics produced in the studio. Utilizing a qualitative descriptive approach, the research thoroughly examines the methods and outcomes involved in choosing suitable dye compositions for agateware production. The findings highlight that the application of multiple colors—such as white, blue, orange, and others—results in intricate and visually balanced patterns that elevate the artistic value of the ceramics. These combinations not only contribute to the aesthetic uniqueness of each piece but also reflect the craftsmanship and innovation involved in the production process. The study also considers how different dye compositions influence consumer perception, suggesting that color harmony can significantly affect a product's desirability in the marketplace. Furthermore, the research emphasizes the potential for dye composition to impact market competitiveness by aligning product aesthetics with current design trends and consumer preferences. The insights gained from this study are expected to support the development of more innovative, visually compelling, and marketable agateware ceramics at Lukita Ceramic Studio. By refining color application techniques, the studio can strengthen its artistic identity and broaden its appeal to a wider audience.